2023
DOI: 10.3390/vaccines11071207
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy Phenomenon Evolution during Pregnancy over High-Risk Epidemiological Periods—“Repetitio Est Mater Studiorum”

Abstract: (1) Background: The recent epidemiological events were high-stress level generators for humanity, particularly for pregnant women, influencing their attitude, behavior, and decisions regarding vaccination during pregnancy or regarding their future child. The aim of this study was to analyze the anti-pertussis vaccination decision-shaping factors in pregnant women during two epidemiological periods: the measles epidemic and the COVID-19 pandemic. (2) Methods: Two groups of pregnant women were invited to be part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…In studies conducted by Fathi et al and Mohsen et al, it was found that physicians and health staff were effective in promoting preventive behaviors [35,42]. Physicians were also identified as the most important source of information, and educational programs had an important influence on the behavior of the parents concerning treating or preventing children's diseases [43][44][45]. The study conducted by Biezen et al shows that communication between GPs and parents is therefore a vital component in reducing antibiotic prescribing in general practice [46].…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted by Fathi et al and Mohsen et al, it was found that physicians and health staff were effective in promoting preventive behaviors [35,42]. Physicians were also identified as the most important source of information, and educational programs had an important influence on the behavior of the parents concerning treating or preventing children's diseases [43][44][45]. The study conducted by Biezen et al shows that communication between GPs and parents is therefore a vital component in reducing antibiotic prescribing in general practice [46].…”
Section: Discussionmentioning
confidence: 99%
“…On February 19, 2024, a Memorandum of Understanding on the establishment of Turkey-Azerbaijan University was signed between the Ministry of Science and Education of the Republic of Azerbaijan and the Higher Education Council of the Republic of Turkey in Ankara (6). This is one of the important steps taken regarding our education.…”
mentioning
confidence: 99%